2021
DOI: 10.1080/10667857.2021.1915056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of slicing parameters on surface quality and mechanical properties of 3D-printed CF/PLA composites fabricated by FDM technique

Abstract: The carbon fiber reinforced polymer matrix composites play an important role in many applications, due to their high strengths and moduli. Hence, this present study focuses on evaluation of mechanical properties of three dimensional (3D)-printed carbon fiber/polylactic acid (CF/PLA) composites, using fused deposition modeling (FDM) technique. The composites were prepared with different slicing parameters: layer heights or thicknesses (0.08, 0.25 and 0.64 mm), infill densities (20, 40, 60 and 80%) and layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 32 publications
2
17
0
3
Order By: Relevance
“…Unlike the tensile results (see Figure 7), for the samples containing 1% FW, a notable performance improvement was recorded. Static bending tests indicated that failure in all composite systems tested, occurs due to the activation of compression failure mechanisms 45 on the upper surface of the specimen. This behavior, in the case of the 3D_1%FW specimens, helps to overcome the limits of the technology by compressing the presence of voids in the section.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the tensile results (see Figure 7), for the samples containing 1% FW, a notable performance improvement was recorded. Static bending tests indicated that failure in all composite systems tested, occurs due to the activation of compression failure mechanisms 45 on the upper surface of the specimen. This behavior, in the case of the 3D_1%FW specimens, helps to overcome the limits of the technology by compressing the presence of voids in the section.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 26b shows that the improved mechanical strength was achieved due to adhesion between the carbon fiber and ABS matrix and it shows that the pattern even after the fiber failure, the matrix takes up a load and undergoes larger elongation before complete failure. Figure 26c shows that the main reason for the failure is due to the improper fiber adhesion at the interface and resin breakage takes place [40][41][42][43][44].…”
Section: Fractography Analysis Of Fractured Specimens For Cf-absmentioning
confidence: 99%
“…[ 40 ] investigated the influence of raster angle on mechanical properties of thermoplastic parts under tensile loading and found that parts printed at 45° and 90° exhibit superior mechanical properties. Vinoth Babu et al [ 41 ] studied the impact of variation in slice thickness, infill percentage, and infill deposition strategy on the mechanical performance of thermoplastic composite components. They observed that interlayer bonding is improved at higher slice thickness.…”
Section: Introductionmentioning
confidence: 99%